A comparative study of the flexural behavior of preplaced lightweight aggregate concrete and normal weight reinforced concrete slabs - Islam, Md Shahidul; Pennung Warnitchai; Thanakorn Pheeraphan; Anwar, Naveed; Punchet Thammarak; Government of Bangladesh (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
There are many studies where the concrete mix is designed with locally available light weight resources. Scientists has developed and investigate the mechanical properties of that concrete but the information about the usage of light weight concrete in structural member is very rare. So, it is very essential to investigate the usability of newly invented concrete with different lightweight materials available in local area for structural member. In Thailand, different types of light weight concrete are being used but limited to the nonstructural member. Strength as well as flexural performance are most important for some concrete to be used in a load bearing member. This research is carried out with four types of concrete developed by senior researcher, so it is a continuation of previous work. Out of four concrete, one is normal weight conventional concrete and rest are light weight concrete such as preplaced light weight aggregate concrete (PLWAC), light weight concrete (pumice), light weight concrete (ECA). Among three light wight concrete, one is done by preplaced technique and other two are in cast in place method. Seven slabs with same dimension and reinforcement is cast with different concrete and tested under two point loading test. Then compared the flexural performance of slab member with each other. The load bearing capacity of preplaced light weight aggregate concrete shows almost same behavior as normal weight concrete slab. Vector2, a two-dimensional nonlinear finite element analysis program is used to validate experimental results of reinforced concrete slab member. After comparison of flexural behavior of slab from experimental and numerical analysis, it can be concluded that preplaced light weight aggregate concrete is able to bear the load within the serviceability.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2021
Keywords: Lightweight concrete; Concrete slabs; Aggregates (Building materials)